1998
DOI: 10.2214/ajr.171.6.9843312
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid cystic carcinoma of the breast: mammographic appearance and pathologic correlation.

Abstract: A denoidcysticcarcinomais a rarevariant of adenocarcinoma that usually occursinthemajorand minor salivary glands. Nevertheless, tumors with this patternhavebeenobservedin other organs including the breast, tracheobronchial tree, uterine cervix, larynx, and Bartholin's gland[ 1â€"5]. The cell of origin is obscure, but evidence suggests that it may be derived from the ductal epithelium and myoepithe hum [6]. Pathologically, the presenceof both cell types is necessary for the diagnosis of adenoidcysticcarcinomaof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 9 publications
4
41
2
2
Order By: Relevance
“…On mammography, the majority of the ACCs of the breast present as high-density masses with irregular or lobulated shape and indistinct margins, which have been described as malignant-appearing (8,(16)(17)(18)(19); these characteristics were consistent with our findings. The sonographic appearance of ACC has been described as a hypoechoic or heterogeneous mass with irregular, lobulated or oval contours and unclear margin (7,8,18).…”
Section: Discussionsupporting
confidence: 91%
“…On mammography, the majority of the ACCs of the breast present as high-density masses with irregular or lobulated shape and indistinct margins, which have been described as malignant-appearing (8,(16)(17)(18)(19); these characteristics were consistent with our findings. The sonographic appearance of ACC has been described as a hypoechoic or heterogeneous mass with irregular, lobulated or oval contours and unclear margin (7,8,18).…”
Section: Discussionsupporting
confidence: 91%
“…ACC may present as a cir- © C I C E d i z i o n i I n t e r n a z i o n a l i cumscribed lobulated nodule in mammography. When the limits of the nodular shadow were not clear, microscopic invasion was usually present (30). Our case did not present these characteristics though.…”
Section: Discussioncontrasting
confidence: 55%
“…Tsuboi et al (31) reported that mammary ACC could be distinguished from conventional types of breast carcinoma by dynamic MRI. Santamaria et al (30) discovered that the majority of carcinomas were located in the upper quadrant of the breast or in the area of the areola. ACC may present as a cir- © C I C E d i z i o n i I n t e r n a z i o n a l i cumscribed lobulated nodule in mammography.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, simple lumpectomy is not recommended due to high local recurrence. Santamaria et al reported high local recurrence rates in patients with simple lumpectomy (17). Leeming et al (18) detected a high local recurrence rate after lumpectomy of 37%.…”
Section: Discussionmentioning
confidence: 99%